2020
DOI: 10.31933/dijms.v2i2.448
|View full text |Cite
|
Sign up to set email alerts
|

The Intention to Adopting Cryptocurrency of Jakarta Community

Abstract: The development of information technology encourages technological growth in the financial sector, namely cryptocurrency. Cryptocurrencies created by private parties still have many shortcomings in terms of security. So it needs an important role from the competent institution. In addition, during the Covid 19 pandemic, cash was considered a medium for spreading the virus. So one of the reasons China started releasing its own digital money was under the strict control of the People's Bank of China. Indonesia i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 10 publications
(12 reference statements)
1
12
0
Order By: Relevance
“…Similarly, Walton and Johnston (2018) discovered that people rather invest in Bitcoin if their social group of family, friends, and peers have a positive attitude towards cryptocurrency and invest in it, which was confirmed by several studies (Boxer & Thompson, 2020;Gazali et al, 2019;Jankeeparsad & Tewari, 2018;Kim, 2021;Schaupp & Festa, 2018). Still, Zamzami (2020) has not found subjective norm as an influencing factor in Indonesia, nor Mazambani and Mutambara (2019) in South Africa, Ullah et al (2021) found its negligible impact in Pakistan, and Arias-Oliva et al ( 2021) discovered it as an enabling factor with a positive influence on intention to use cryptocurrency in Spain.…”
Section: Introduction To Cryptocurrencymentioning
confidence: 75%
See 4 more Smart Citations
“…Similarly, Walton and Johnston (2018) discovered that people rather invest in Bitcoin if their social group of family, friends, and peers have a positive attitude towards cryptocurrency and invest in it, which was confirmed by several studies (Boxer & Thompson, 2020;Gazali et al, 2019;Jankeeparsad & Tewari, 2018;Kim, 2021;Schaupp & Festa, 2018). Still, Zamzami (2020) has not found subjective norm as an influencing factor in Indonesia, nor Mazambani and Mutambara (2019) in South Africa, Ullah et al (2021) found its negligible impact in Pakistan, and Arias-Oliva et al ( 2021) discovered it as an enabling factor with a positive influence on intention to use cryptocurrency in Spain.…”
Section: Introduction To Cryptocurrencymentioning
confidence: 75%
“…Given concerns related to their use and the apprehensiveness of the unknown among potential users (Al-Amri et al, 2019;Sohaib et al, 2019), cryptocurrency use is still limited. There is also scarce scholarly research on the factors influencing the behavioral intention to use cryptocurrency (Abbasi et al, 2021;Al-Amri et al, 2019;Arias-Oliva et al, 2021), mostly based on technology adoption models, with contradictory evidence (Ajzen, 2020;Noreen et al, 2021;Zamzami, 2020), and the limited generalizability of the results (Ter Ji-Xi et al, 2021;Walton & Johnston, 2018), especially in specific cultural contexts such as Saudi Arabian. For these reasons, this study has explored the factors influencing the behavioral intention of Saudi citizens to use cryptocurrencies from human, financial, and security perspectives by combining factors from attitudinal and technology adoption models.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations